FC2 Activating transcription factor 1 co-regulates iron, lipid and anti-inflammatory target genes to direct a novel atheroprotective human plaque macrophage subset. Issue 17 (26th August 2010) - Boyle, J J; Johns, M; Nguyen, A T; Yu, J; Game, L; Schaer, D J; Mason, J C; Haskard, D O
Abstract : Rationale: Monocytes entering tissues, including advanced atherosclerotic plaques, rapidly mature and adapt to their new microenvironment. Intraplaque haemorrhage promotes human atherosclerosis progression and destabilisation via a dual metabolic challenge: cholesterol-enriched erythrocyte membranes and haem-iron. In human coronary culprit lesions, we recently described a novel macrophage subset (M-haem) with atheroprotective properties (IL-10high HO1high CD163high HLADRlow MPOlow 8keto-Guanosinelow). Methodology: We dissected the mechanism of M-haem differentiation by microarray, computational biology and gene manipulation in human primary macrophages and human coronary lesions. Results: Microarray analysis showed that M-haem cells were distinct from conventional M1 or M2 subsets. Using computational biology, we identified a simple transcriptional network motif with activating transcription factor 1 (ATF1) as a hub co-inducing HO1, SOCS1 and NR1H2 (LXR-α). Silencing RNA experiments showed that ATF1 induction was required for haem to upregulate HO-1 SOCS1 and NR1H2. Luciferase analysis confirmed that ATF1 transcriptionally activated both HO-1 and LXR. Luciferase deletion mutants indicated that the key ATF1-site in the HO-1 enhancer was distal (−2.2 kb to −4.9 kb). Binding experiments showed that ATF1 bound to this sequence. ATF1 overexpression in human macrophages conferred the characteristics of M-haem cells, including co-induction of HO-1, NR1H2, resistance to foam cell formation, increased survival and antioxidant protection. Conclusions: Our data define the molecular basis of the differentiation of M-haem, a novel atheroprotective macrophage subset. Our data indicate that redirection of macrophage phenotype in atherosclerosis progression is a modality appropriate for therapeutic development.